Menelusuri Jejak dan Upaya Menghubungkan Sains dan Agama - Kristianto, Paulus Eko (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2018)
Looking for a connection between science and religion to be a struggle of its own throughout history. Many thinkers and schools of thought try to formulate them, among them critical realism, anti-reductionism, creationism, and intelligent design. The hypothetical alignment connection is expected to provide transcontinental, trans-contextual, and global expanse of connections. The stretch here refers to the religion is supposed to illuminate science and vice versa. Science and religion must be strived to enter in the same best condition because both have sought the truth in various ways. If necessary, the connection is attempted to enter into integration, although occasionally it can enter into conflict methodology. Abstrak Mencari hubungan antara sains dan agama menjadi pergumulan sendiri sepanjang sejarah. Banyak pemikir dan aliran pemikiran mencoba merumuskannya, di antaranya realisme kritis, anti reduksionisme, kreasionisme, dan intelligent design. Hubungan kesejajaran hipotetis diharapkan tersedianya bangunan hubungan bersifat transkontinental, transkontekstual, dan bentangan-bentangan global. Bentangan di sini merujuk pada agama diharapkan harus menerangi sains, dan sebaliknya. Sains dan agama harus diupayakan masuk dalam kondisi yang sama-sama terbaik karena keduanya telah mencari kebenaran https://colindancias.uvt.ro/ dengan berbagai jalan. Bila perlu, hubungan itu diupayakan masuk pada integrasi, walaupun sesekali bisa masuk ke metodologi konflik.